Persepsi guru-guru sekolah menengah terhadap kaunselor sekolah : kajian terhadap guru-guru sekolah menengah sekitar Kuching - Jeffery, Apdal (Universiti Malaysia Sarawak (UNIMAS), 2004)
This research was carried out to identify the secondary school teacher perceptions towards counselor. It involved the secondary school teachers in Kuching, Sarawak Specifically, the research is to investigate the level of counselor activation in school, the relationship between the teachers and the counselor, the teachers' willingness to consult in counselor, the teachers' confidence towards counselor abilities and teacher's level of understanding towards counselor role and function. It also looks at other two factors, factor that influences teacher's acceptance towards counselor and factor that leads teacher for not using counselor services in school. The questionnaire used in this research is by applying the survey research method to collect the data. The respondents of this research consists of 90 teachers represent both genders. The data collected is analyzed using the Statistical Package for the Social Sciences (SPSS) Program version 11.5 for Windows. This research was a quantitative research and the data collected is analyzed by using the descriptive statistic (min) and the Pearson Correlation Test. There are 15 hypotheses of teachers' perceptions towards school counselors, and 4 of them are accepted. Generally finding show that teacher perception towards counselor based on selected demographical factors is not different. This can be seen on the highest min value for all aspects of teacher perception towards the counselor activation level in school, the relationship between teacher and counselor, the teacher willingnes to consult with counselor, the teacher confidence towards counselor's ability and teacher's level of understanding towards counselor role and function. Based on the outcomes of the finding, referring to the factors of teachers' acceptance towards counselor, it is indicated that the attempts of counselor to express interest to help had been the choice of teachers. Meanwhile, teacher's rejection factor towards counselor is because of low self-esteem to discuss and express problems to counselor.